Environmental filtering rather than phylogeny determines plant leaf size in three floristically distinctive plateaus - Tingting Ren (Elsevier, 2021)
Leaf is essential for plant growth and development; however, the relative importance of environmental filtering and phylogeny in determining leaf size across different spatial scales in grassland ecosystems remains poorly explored. We used transect methodology to explore the spatial variation in leaf size and its underlying mechanisms in grasslands along three topographically and floristically distinctive plateaus in northern China. We measured leaf size of a total of 1192 grassland species in the Tibetan Plateau (TP, temperature limited), Loess Plateau (LP, soil-nutrient limited), and Mongolia Plateau (MP, precipitation limited) along three transects encompassing meadow, typical, and desert steppes. Leaf size ranged from 0.01 to 258.16 cm2, with an average of 5.54 cm2. The smallest leaves were measured in the TP. At the vegetation association level, the largest leaves were present in the meadow steppe, followed by those in typical and desert steppes, irrespective of the plateau. Unexpectedly, phylogeny had a negligible effect on the spatial variation in leaf size in the grasslands. Leaf size was positively correlated with growing-season temperature and precipitation but negatively correlated with ultraviolet (UV) radiation, suggesting that environmental filtering plays a more important role in affecting leaf size than phylogeny. Furthermore, leaf size in the TP and MP was mainly affected by precipitation and UV radiation, respectively, whereas that in the LP was affected by temperature, precipitation, soil nutrients and UV light. Specifically, our results underscored the importance of environmental filtering rather than phylogeny in determining plant leaf size and shed light on the unexpected role of UV radiation in contributing to leaf size variations in these plateaus. Our study provides novel insights into the response of plants to global change, especially in plateaus, alpine zone, and high-latitude areas.